GENETIC MECHANISMS AND CLINICAL AND DIAGNOSTIC FEATURES OF CONGENITAL ANOMALIES OF SEXUAL DEVELOPMENT - Negmadjanov Bakhodur Boltayevich; Makhmudova Sevara Erkinovna (Web of Journals Publishing, 2025)
Infertility is often caused by congenital anomalies of sexual development and is associated with an unfavorable reproductive prognosis. In recent years, the development of assisted reproductive technologies has significantly improved the reproductive prognosis of infertile patients. Improvement of reproductive prognosis in congenital anomalies of sexual development largely depends on timely diagnosis of anomalies and rational management of patients
Keywords: Congenital anomalies of genital development, bicornuate uterus, genetics, diagnosis, aplasia of uterus and vagina.